Screening of rice proteins using 2-d gels after inoculation with Rhizotonia solani - Morela Delgado, Fuchs (2021)
Sheath blight caused by Rhizotonia solani is described as the second major disease affecting rice. Genetic resistance to R. solani the ideal control measure is hampered because of the difficulty in identifying adequate resistance sources under typical selection conditions. Proteomic analysis techniques using two-dimensional gels (2D-PAGE) allow the study or monitoring of global changes in protein expression under normal and stress conditions. In this work, we compared rice leaves protein expression patterns of two Venezuelan varieties 12, 24 and 48 h after inoculation with R. solani. Approximately 400 and 300 protein spots stained with Sypro Ruby were reproducibly resolved across gel replicates, for PALMAR and FONAIAP-2000, respectively. Forty proteins out of a total 49 were identified for PALMAR variety, with thirty-two up-regulated protein spots and 8 down-regulated. Twenty-six proteins out of a total 33 were identified for FONAIAP-2000 variety, with seven up-regulated protein spots and 19 down-regulated. RuBisCo was the protein most identified (48% and 82% of the detected proteins for PALMAR and FONAIAP-2000, respectively). Other identified proteins showing variations were ATPase beta subunit, UDP-glucose anthocyanin 5-O-glucosyltransferase, RNA-binding protein, putative transkelotase 1, putative ferredoxin-NAPD(H) oxide-reductase, and putative 33kDa oxygen evolving protein photosystem II. Based on our results, rice response to R. solani could be described where energy is required to induce a defense and it is supplied by proteins involved in energy metabolism. According to this, proteomic could provide information and insights on the response of rice to challenge with R. solani and other pathogens.